HISTORY AND MORALITY XXI SHISHKIN READINGS REVUE - S. M. Medvedeva (Vestnik MGIMO-Universiteta)
23d December 2016 the Department of Philosophy of MGIMO-University conducted annual XXI Shishkin Readings in memory of famous Russian philosopher A. F. Shishkin, the founder of the Department of Philosophy in MGIMO. The participants of the event from MGIMO-University were the following: professor A.V. Shestopal (Doctor of Philosophy), professor T.V. Panfilova (Doctor of Philosophy), professor M.A. Muntyan (Doctor of Philosophy), M.V. Silanteva (Doctor of Philosophy), associate professor M.V. Harkevich (PhD), associate professor A.N. Samarin (PhD), associate professor S.N. Lutova (PhD), associate professor D.N. Belova (PhD), professor VS. Glagolev (Doctor of Philosophy). The invited guests of the University were the following: Chef Researcher of Institute of Philosophy professor K.M. Dolgov (Doctor of Philosophy), director of scientific-producing company "Didactic", president of "Consortium Educational Environment" A.S. Ignatenko-Lamsdorff, director of the Center for International Relations M. Halil. Also in the conference participate the postgraduate students from different departments: D.C. Gorshenev, U.A. Hailova, A.U. Belenko, etc.